Seal Slab Prestressed Pile Interface Bond From Full-Scale Testing - Gray Mullins (Deep Foundations Institute, 2013)
This paper presents experimental results from a study to assess the interface bond between a cast-in-place concrete seal slab and prestressed concrete piles in cofferdams. Three different seal slab placement conditions - fresh water, salt water and bentonite slurry - were evaluated and the results compared against controls where no fluid had to be displaced by the concrete. Normal pile surfaces were investigated. Additionally, the situation of ?soil caked? piles was also investigated. Both model and full-scale tests were conducted. In the model tests, twenty eight 15 cm square prestressed sections were used with the embedment depth varied between d-2d, where d is the width of the pile. In the full-scale tests, 16 specimens were tested. The prestressed piles were 36 cm square with the embedment varied between 0.5d-2d. Four of the sixteen piles were cast with embedded gages located at the top, middle and bottom of the interface region. The results showed that loads were transferred to the piles over an effective area, not the entire embedded depth. Significant bond stresses developed even for the worst placement condition. Recommendations are made for revising current values in specifications.